2018
DOI: 10.29303/jppipa.v4i2.113
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Hasil Belajar Fisika Peserta Didik

Abstract: Abstrak - Tujuan penelitian ini adalah untuk mengetahui pengaruh model pembelajaran inkuiri terbimbing terhadap hasil belajar fisika peserta didik. Jenis penelitian ini adalah quasi experiment dengan desain penelitian kelompok non-ekuivalen. Pengambilan sampel menggunakan teknik purposive sampling, sehingga diperoleh kelas XI MIA 1 sebagai kelas eksperimen dan kelas XI MIA 2 sebagai kelas kontrol di SMAN 6 Mataram. Instrumen penelitian berupa tes pilihan ganda sebanyak 30 soal yang telah diuji validitas, relia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 5 publications
1
35
0
15
Order By: Relevance
“…The research by Nurhidayati, et al (2015) also showed that the combined STAD combined with guided inquiry method could increase the activity and learning outcomes of students with a very high percentage.…”
Section: Resultsmentioning
confidence: 97%
“…The research by Nurhidayati, et al (2015) also showed that the combined STAD combined with guided inquiry method could increase the activity and learning outcomes of students with a very high percentage.…”
Section: Resultsmentioning
confidence: 97%
“…Berdasarkan hasil pengamatan peneliti di kelas II SDN Wonorejo 01 menunjukkan bahwa proses pembelajaran masih konvensional dengan model pembelajaran ceramah. Kegiatan pembelajaran masih berpusat pada guru, sehingga peserta didik hanya mendengarkan materi (Nurmayani & Doyan, 2018). Hal ini menyebabkan peserta didik merasa jenuh dan kurang termotivasi untuk belajar (Sulfemi & Minati, 2018).…”
Section: Pendahuluanunclassified
“…These factors include the learning methods used by the teacher, student motivation and readiness, facilities and learning resources. The learning model or approach used by the teacher is expected to direct students to be active and creative, so that learning becomes learnercentered (Nurmayani, 2018).…”
Section: Introductionmentioning
confidence: 99%